Donner naissance: doulas, sages-femmes & justice reproductive - Apfel, Alana; Ross, Loretta J.; Law, Victoria; Federici, Silvia; Pruvost, Geneviève; Tincelin, Adel (Cambourakis, 2024)
Donner naissance . Doulas, sages-femmes & justice reproductive . Alana Apfel nous propose un recueil vivant de treize récits écrits par des doutas, des sages-femmes et des activistes féministes aux États-Unis qui racontent la naissance autrement. Au modèle de la toute-puissance médicale qui saurait mieux que les femmes elles-mêmes ce qu'est un « bon » accouchement est opposé ici un tout autre professionnalisme, à la fois discret et attentif, qui permet de faire une juste place à des femmes indignement traitées. Militer pour la « justice reproductive », c'est créer des « communs » de la naissance, selon la formule de Silvia Federici dans son introduction.. La postface de Geneviève Pruvost nous rappelle que l'obstétrique française est la plus médicalisée d'Europe. À l'heure où, en France, les sages-femmes à domicile font l'objet d'une tentative d'éradication professionnelle, Donner naissance nous propose une nouvelle manière de penser les trajectoires reproductives et nous fournit les outils théoriques et pratiques nécessaires
Section: 1 vol. (262 p.) : ill. ; 18 cm.
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; care; corps; cours; discipline; justice reproductive; justice sociale; maternité; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis

La peur au ventre (Babel films, 2024)
En procédant à l’invalidation de l’arrêt Roe v. Wade, qui légalisait l’avortement aux États-Unis depuis 1973, la Cour suprême a fait un saut en arrière. Ce recul est symptomatique d’une polarisation déroutante. Dérangée par cette situation, la réalisatrice et féministe Léa Clermont-Dion s’interroge : comment ce précédent juridique aura de l’impact chez nous, au Canada ? Elle offre une exploration de la montée des groupes antiavortement au Québec, et partout au pays, mais présente aussi une plongée rare dans la riposte féministe et pro-choix qui s’organise. Après son film coup de poing Je vous salue salope : la misogynie au temps du numérique (2022), la cinéaste poursuit sa quête de justice et de vérité.
Place: Montréal
Keywords: approches et analyses; avortement; canada; discipline; discours dominant; droits des femmes*; histoire; histoire des femmes*; justice reproductive; justice sociale; militance; pro-choix; régions géographiques; santé; santé des femmes*; sciences humaines; sociologie; systèmes d'oppressions; thématiques; états-unis

Synthèse des connaissances sur la notion renouvelée de charge mentale : constats et invisibilités sur la santé et le bien-être des femmes - Courcy, Isabelle; St-Charles, Johanne; Lefrançois, Mélanie (2023)
Qu’elles se réalisent dans le contexte du travail rémunéré ou dans la vie personnelle, ces tâches se révèlent complexes, voire parfois impossibles à articuler entre elles. La charge mentale affecte plus fortement les femmes1 qui assument une part plus importante dans les tâches domestiques et le soin aux proches. En collaboration avec des représentantes de groupes communautaires et de la société civile concernés par l’équité de genre et la justice environnementale, cette synthèse des connaissances porte sur la charge mentale et ses effets sur la santé des femmes. Quatre messages clés sont à retenir : 1) Les effets de la charge mentale sur la santé des femmes sont nombreux; 2) Il importe de comprendre la charge mentale comme un construit complexe et multifacettes afin de développer des interventions durables et équitables ; 3) Le travail associé à la charge mentale est « invisible » en raison de la gestion émotionnelle et morale et du travail cognitif qu’il comporte, et parce qu’il n’est pas reconnu ou non comptabilisé dans l’économie de marché néolibérale; 4) Les manifestations de la charge mentale prennent des formes différentes qu’il importe d’analyser avec une approche féministe intersectionnelle. Cinq axes regroupant des recommandations et des pistes de solution sont proposés. Axe 1 : Reconnaître la nature complexe de la charge mentale et ses stéréotypes associés. Axe 2 : Soutenir le travail de care dans les milieux de travail. Axe 3 : Améliorer les services de soins et de soutien à la famille offerts à la population et offrir un accès équitable à ces ressources. Axe 4 : Prendre en compte la charge mentale dans les politiques publiques et créer les instances pour assurer des actions de prévention en temps de crise. Axe 5 : Inciter et normaliser le travail de care assumé par les hommes.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; care; charge mentale; discipline; environnement; inégalités; justice sociale; patriarcat; périodes historiques; québec; régions géographiques; santé; santé des femmes*; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; travail; travail des femmes*; travail du care

Les allongées: Femmes en douleur, seules et ensemble - Simard, Valérie (La Presse, 2022)
Atteintes de douleurs chroniques, cycliques ou spontanées, les allongées ont en commun leur posture. Leur solitude aussi, malgré l’addition de leurs voix. Elles-mêmes aux prises avec des douleurs fréquentes, Martine Delvaux et Jennifer Bélanger rendent hommage à ces femmes, dans Les allongées, un livre sur la souffrance et la résilience.
Keywords: approches et analyses; arts; corps; discipline; douleurs physiques; femmes*; justice sociale; littérature; ressource en ligne; revue de presse; santé; santé des femmes*; thématiques; études littéraires

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Au-delà de la COVID-19: un plan féministe pour la durabilité et la justice sociale - Staab, Silke; Tabbush, Constanza; Turquet, Laura; Williams, Loui (ONU Femmes, 2021)
Alors que le monde apprend à vivre avec le COVID-19, à « reconstruire en mieux » et est mobilisé pour sortir de la crise actuelle, le nouveau « Plan féministe » d’ONU Femmes fournit une feuille de route visionnaire mais concrète visant à placer l’égalité des sexes, la justice sociale et la durabilité au centre de la relance et de la transformation. Le COVID-19 a révélé et aggravé les inégalités et rappelle à quel point les économies et les démocraties du monde sont insoutenables et fragiles. La crise met également en garde contre les changements climatiques et la dégradation de l'environnement imminents. Ceci a créé à la fois le besoin et l’opportunité de repenser les politiques économiques et sociales et de réévaluer ce qui doit être priorisé. Le « Plan féministe » cartographie les politiques ambitieuses et transformatrices relatives aux moyens de subsistance, aux soins et à l'environnement qui sont nécessaires pour construire un avenir plus équitable et durable. Pour y parvenir, il appelle à des approches politiques spécifiques au contexte, à des stratégies politiques adaptées et à un financement. Le plan identifie les leviers clés qui peuvent créer un changement ainsi que les actrices et acteurs aux niveaux mondial, national et local qui doivent prendre des mesures pour avancer vers cette vision.
Keywords: 2000 à aujourd'hui; OFDIG; approches et analyses; covid-19; droits des femmes*; femmes*; inégalités; justice sociale; politique; périodes historiques; ressource en ligne; santé; systèmes d'oppressions; thématiques

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences

Introduction: care aux Suds Quand le travail de care interroge les inégalités sociales - Borgeaud-Garciandía, Natacha; Guimarães, Nadya Araujo; Hirata, Helena (Revue internationale des études du développement, 2020)
Cet article introductif fait la lumière sur certains aspects de la production et de l’organisation du care dans des pays et régions dits « du Sud ». Partant d’une définition large du care, qui inclut ses dimensions sociales, politiques et éthiques, et des connaissances élaborées dans différents pays du Sud, trois thèmes centraux sont développés : le genre du care, les présences et carences de l’État, et les relations entre migrations et care. Ces thèmes sont sous-tendus par le rôle que jouent le care et sa distribution sociale sur les inégalités sociales et leur reproduction. L’article souligne à quel point nombre de travaux élaborés dans les Suds permettent d’interroger et d’enrichir la perspective du care et ses schémas explicatifs.
Keywords: approches et analyses; care; cours; justice sociale; migration; pol4022; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; thématiques; travail; éthique; éthique du care

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

(Re)penser l’accès aux espaces intimes en contexte de handicap intellectuel: une question de droit et de participation sociale - Pariseau-Legault, Pierre; Holmes, Dave (Revue générale de droit, 2017)
En contexte de handicap, la question de l’accès est constituée généralement de l’éventail des aménagements individuels et collectifs nécessaires afin de faciliter l’occupation d’espaces publics. A contrario, peu de choses sont dites à propos des aménagements possibles et potentiels requis afin de sécuriser l’espace privé des personnes identifiées comme ayant un handicap intellectuel. Ce sont pourtant ces lieux intimes, au sein desquels se développent et se déploient l’identité et l’expression affectives, qui sont susceptibles de contribuer à une reconnaissance plus soutenue de l’identité affective et de la citoyenneté sexuelle de ces personnes. Inspirée par les théories d’Erving Goffman et de Michel Foucault, une analyse phénoménologique interprétative (API) fut réalisée auprès des personnes ayant un handicap intellectuel et de leurs proches aidants afin d’explorer cette situation. Nos constats préliminaires suggèrent l’existence d’un processus de négociation complexe des acteurs, des lieux et des moments nécessaires afin de favoriser le développement de la vie affective et sexuelle. De ce fait, trois modes d’existence semblent cohabiter au sein d’une matrice complexe : la dépossession, l’habitation et l’occupation des espaces de socialisation et d’expression affective. Il est proposé d’aborder cette problématique en tant que dynamique géopolitique intégrant les processus d’exclusion des pratiques sexuelles des espaces privés, leur projection dans des espaces publics et, finalement, la juxtaposition de ces deux sphères, publique et privée dans des espaces mixtes. Nous discuterons enfin des implications de cette réflexion sur la « question de l’accès » et sur les politiques publiques visant à diminuer la discrimination systémique ciblant les personnes identifiées comme ayant un handicap intellectuel.
Keywords: approches et analyses; capacitisme; care; corps; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; ressource en ligne; santé; science politique et droit; science politique et droit de la santé; sciences; sciences de la santé; sciences politiques; sex1920; sexualité; systèmes d'oppressions; thématiques

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

Re-thinking HIV-Related Stigma in Health Care Settings: A Qualitative Study - Gagnon, Marilou (Journal of the Association of Nurses in AIDS Care, 2015)
People living with HIV (PLWH) continue to endure stigma and discrimination in the context of health care. This paper presents the findings of a qualitative study designed to (a) describe stigmatizing and discriminatory practices in health care settings, and (b) explore both symbolic and structural stigma from the perspectives of PLWH. For the purpose of this qualitative study, 21 semi-structured in-depth interviews were conducted in the province of Quebec, Canada. The data were analyzed following the principles of thematic analysis. During analysis, three themes were identified, and relations between these themes were delineated to reflect the experiences of participants. The findings suggest that HIV-related stigma in health care settings is episodic in nature. The findings also suggest that HIV-related stigma is experienced through interactions with health care providers (symbolic stigma) and, finally, that it is applied systematically to manage risk in the context of health care (structural stigma).
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; inégalités; justice sociale; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

La justice reproductive, ou l'application du prisme de la justice sociale à la santé et aux droits sexuels, reproductifs et maternels - Fédération du Québec pour le Planning des naissances (Fédération du Québec pour le planning des naissances, 2014)
La justice reproductive est à la fois un cadre d’analyse et de pratiques et un mouvement social qui a émergé aux États-Unis pendant les années 1990. Le terme a été consacré par des femmes africaines-américaines lors de la Conférence internationale sur la population et le développement qui a eu lieu au Caire en 1994. Il est le résultat de l’amalgame entre « justice sociale » et « droits reproductifs ». La justice reproductive situe l’accomplissement de la pleine autonomie sexuelle et reproductive des femmes et des filles au sein d’un projet plus large de justice sociale. Ce mouvement a émergé de l’initiative de femmes racisées et autochtones et continue d’être majoritairement porté par elles.
Keywords: amérique du nord; amériques; approches et analyses; avortement; canada; droits des femmes*; femmes* autochtones; femmes* racisées; inégalités; justice reproductive; justice sociale; maternité; privilèges; québec; racisme; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; états-unis

The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Section: 439 pages : illustrations (certaines en couleur) ; 22 cm
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires

Médecine et sexualité, aperçus sur une rencontre historiographique (Recherches francophones, époques moderne et contemporaine) - Chaperon, Sylvie; Hanafi, Nahema (Clio. Femmes, Genre, Histoire, 2013)
Cet article rappelle dans quelles circonstances une histoire de la sexualité construite à partir de sources médicales a émergé en France dans les années 1970. Il insiste surtout sur les pionnier-e-s de cette histoire pour les périodes moderne et contemporaine et les sources qu’ils et elles ont utilisées. Enfin il met en avant le renouvellement récent de ce champ grâce à une histoire « par en bas ».
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; justice sociale; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Section: xiii, 258 pages : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Luttes XXX : inspirations du mouvement des travailleuses du sexe - Mensah, Maria Nengeh; Toupin, Louise; Thiboutot, Claire (Les éditions du remue-ménage, 2011)
Depuis 1973, des travailleuses et travailleurs du sexe aux quatre coins de la planète se regroupent et se mobilisent. Qui sont ces personnes, comment s’organisent-elles et pourquoi revendiquent-elles la décriminalisation de leur travail? Qu’ont-elles à dire à propos du syndicalisme, du féminisme, de la lutte contre le sida, de la violence ou des phénomènes migratoires? Tout en situant le mouvement des travailleuses du sexe dans son contexte historique et international, cette anthologie unique propose une sélection de documents inédits ou traduits en français pour la première fois. Luttes XXX nous invite à la rencontre d’un mouvement social méconnu. Ici, les voix des travailleuses et travailleurs du sexe, longtemps réduites au silence, s’élèvent, réclament justice.
Keywords: anthologie; approches et analyses; cours; discours dominant; droits des femmes*; fem1000; international; inégalités; justice sociale; mouvements sociaux; premier cycle; santé; systèmes d'oppressions; thématiques; travail; travail du sexe; témoignage

A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

Le droit à l’avortement, une lutte exemplaire - Revue À bâbord ! - bâbord!, Revue À (2008)
Militante de longue date pour le droit à l’avortement, Louise Desmarais publie en 1998 La lutte pour le droit à l’avortement, histoire d’une bataille inachevée. Elle présente ici les principales caractéristiques et les moments forts, selon elle, de la lutte pour le droit à l’avortement au Québec.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; approches et analyses; avortement; canada; care; corps; cours; discipline; histoire; justice reproductive; justice sociale; militance; pol4102; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social

Les femmes dans le champ de la santé : de l’oubli à la particularisation - Membrado, Monique (Nouvelles Questions Féministes, 2006)
L’objectif de cet article est de montrer que la réduction de la santé des femmes à leurs capacités procréatrices structure les représentations médicales à leur égard mais aussi leurs expériences de santé, et qu’elle constitue une véritable impasse pour la construction d’un cadre d’intelligibilité qui prenne en compte l’ensemble de leurs expériences. Je l’illustre à travers les catégories médicales et sociales de l’alcoolisme féminin et le rapport des femmes au cancer du sein. Enfin, je propose des pistes autour de l’intérêt porté aux trajectoires des femmes de manière à rendre visibles dans le champ de la santé les effets structurels de leur place dans la division sexuée du travail et des activités sociales.
Number: 2 Place: Lausanne Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; discours dominant; europe; france; justice reproductive; justice sociale; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
https://digitalcommons.wcl.american.edu/cgi/viewcontent.cgi?article=1284&context=jgspl
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppressions; thématiques; états-unis

From Social Construction to Social Justice: Transforming How We Teach about Intersexuality - Koyama, Emi; Weasel, Lisa (Women's Studies Quarterly, 2002)
Keywords: LGBTQIA2+; approches et analyses; capacitisme; corps; cours; discipline; intersexuation; justice sociale; premier cycle; pédagogie; santé; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences